2020
DOI: 10.47440/jafe.2020.1404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weed management on the growth and yield performances of boro rice cultivars

Abstract: An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during the period from December 2017 through May 2018 to evaluate the effect of weed management practices on the performance of boro rice cultivars. The experiment consisted of three boro rice cultivars viz., BRRI dhan28, BRRI dhan29 and BRRI dhan74 along with six different weed management practices such as no weeding, application of preemergence herbicide Superhit, application of early post-emergence h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
1
0
0
Order By: Relevance
“…Application of pre-emergence herbicides pretilachlor interfered with the growth and development of weeds by inhibiting the cell division and effectively controlled the germinating weeds or emerging weeds during early stages of crop growth followed by hand weeding at later stage and maintain the crop free from crop weed competition for nutrients, space and light resulting in higher number of tillers, number of panicles, grains panicle -1 and ultimately yield. Similar findings were reported by Paul et al (2019), Tasmin et al (2019), Salam et al (2020) and Bhattacharya et al (2022). Interaction effect of date of transplanting and integrated weed management on grain yield was found to be significant (Table 3b).…”
Section: Yieldsupporting
confidence: 87%
“…Application of pre-emergence herbicides pretilachlor interfered with the growth and development of weeds by inhibiting the cell division and effectively controlled the germinating weeds or emerging weeds during early stages of crop growth followed by hand weeding at later stage and maintain the crop free from crop weed competition for nutrients, space and light resulting in higher number of tillers, number of panicles, grains panicle -1 and ultimately yield. Similar findings were reported by Paul et al (2019), Tasmin et al (2019), Salam et al (2020) and Bhattacharya et al (2022). Interaction effect of date of transplanting and integrated weed management on grain yield was found to be significant (Table 3b).…”
Section: Yieldsupporting
confidence: 87%
“…On the other hand, single herbicides reduce weed density of one or two species, which helps to grow others weeds, and they grow vigorously and consume more resources, resulting in poor crop plant growth. This result supports the findings of Salam et al (2020), who reported that benefit cost ratio varied among different rice varieties. Sunil et al ( 2010) also reported that pre-emergence application of bensulfuron methyl + pretilachlor (6.6 GR) @ 0.06 + 0.6 kg ha -1 + one inter cultivation at 40 DAS recorded significantly higher grain and straw yields (4425 and 5020 kg ha -1 ), lower weed population and dry weight (17 and 2.32 g m -2 ).…”
supporting
confidence: 92%